Fiber Optic Laboratory Development Model in Vocational High School - sa'adah, nurul laili; widiyanti, widiyanti; Yoto, Yoto (Fakultas Teknik Universitas Negeri Malang, 2021)
Technological developments make telecommunications networks through internet access an urgent matter due to the increasing human need for communication. The purpose of this study was to describe the development model of a fiber optic laboratory in order to improve students and teachers’ competency. This research used a descriptive qualitative case study method at Public Vocational High School (PVHS) of Dwija Bhakti 1 Jombang. The results stated that the fiber optic laboratory development model is used to print graduates to have competencies that are in accordance with their fields and are expected to be able to compete in the industrial world. Schools collaborate with industry through the provision of fiber optic laboratories as an effort to improve these competencies. By conducting several stages, namely applying the MoU, affording the tools, branding and mocking-ups. In addition, there are teacher training and certification activities followed by curriculum implementation, student certification and the last is activity evaluation. It can be concluded that the development of fiber optic laboratory procurement at Public Vocational High School (PVHS) of Dwija Bhakti 1 Jombang has been in accordance with the agreement between the Ministry of Education and Culture with PT Telkom regarding the link and match curriculum in the field of fiber optic.